2017
DOI: 10.1016/j.juro.2017.01.036
|View full text |Cite
|
Sign up to set email alerts
|

Multiparametric Magnetic Resonance/Ultrasound Fusion Prostate Biopsy: Number and Spatial Distribution of Cores for Better Index Tumor Detection and Characterization

Abstract: Approaching magnetic resonance imaging/transrectal ultrasound fusion targeted biopsy with a single core might be inadequate. Rather, taking 2 cores in the center of the index lesion may provide more accurate cancer detection and optimize the chances of finding the highest Gleason pattern.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(37 citation statements)
references
References 24 publications
2
35
0
Order By: Relevance
“…Additional focal perilesional saturation with four cores has been suggested to reduce the risk of missing or undersampling the lesion [2]. Consistent with two recently published studies by Porpiglia et al [30,31] and Kenigsberg et al [30,31], our present study showed that a high diagnostic yield can be achieved for all different PI-RADS lesions with a median of two TBx cores per lesion. Rather than adhering to a fixed number of biopsy cores, we believe that individual biopsy operators should critically evaluate their own TBx outcomes with imaging and pathological feedback to determine how to optimise MRI-TRUS-fusion biopsy in their own hands.…”
Section: Discussionsupporting
confidence: 91%
“…Additional focal perilesional saturation with four cores has been suggested to reduce the risk of missing or undersampling the lesion [2]. Consistent with two recently published studies by Porpiglia et al [30,31] and Kenigsberg et al [30,31], our present study showed that a high diagnostic yield can be achieved for all different PI-RADS lesions with a median of two TBx cores per lesion. Rather than adhering to a fixed number of biopsy cores, we believe that individual biopsy operators should critically evaluate their own TBx outcomes with imaging and pathological feedback to determine how to optimise MRI-TRUS-fusion biopsy in their own hands.…”
Section: Discussionsupporting
confidence: 91%
“…These studies also document low yields of sampling normal-appearing nonadjacent sextants that do not alter overall risk stratification in the majority of patients with a cancer diagnosis (Fig 2) (8,35,67). Multiple analyses indicate that when targeted biopsies are performed, additional cores (so-called focal saturation) increase biopsy yields (67,(69)(70)(71)(72); however, the optimal number of focal saturation biopsy cores remains undefined (8,69,70,73).…”
Section: Patient Implications After Intermediate-or High-likelihood Mmentioning
confidence: 99%
“…In the present study, TB cores were taken from the central area of MRI-suspicious lesions, because a higher prevalence of cancer with higher grades was expected in the central area of the targets rather than in their peripheral area. 6 Among the men with TBmissed SC and upgrading, however, 29% (6/21) and 33% (16/49) were diagnosed by SB cores inside targets, respectively, which were sampled from peripheral areas of targets in most cases. Although further spatial analysis of MRI-identified but TB-missed cancers is necessary, TB that samples both the central and peripheral areas of targets could improve clinically important cancer detection.…”
Section: Discussionmentioning
confidence: 94%
“…5 In the MRI and TB era, SB detects MRI-missed cancer from outside targets and MRI-identified cancer from inside targets incidentally. When TB is further improved technically and strategically, MRI-identified but TB-missed cancer from inside targets would decrease, 6 and the detection of MRI-missed adverse pathology, such as SC and upgrading only from outside targets, would become the main role of SB. In the present study, we explored the characteristics of patients with clinically important pathology only from outside targets, to tailor prostate biopsy to the individual in accordance with MRI findings.…”
Section: Introductionmentioning
confidence: 99%